Latvian Consulate in Klaipėda (1920–1940) - Gervetauskaitė, Edita (History / Istorija, 2019)
Based on the analysis and synthesis of primary sources (the article makes use of the material from thirteen funds from the Lithuanian Central State Archives (hereinafter – LCSA), information from published documents, statistical publications and the periodical press of the region), the article analyses the stages of development of the Latvian consulate in Klaipėda in 1920–1940. It specifies the circumstances of establishment, functioning and closure of the Latvian consulate; the cases of consuls – Alfreds Misse, Peteris Kalcenavs, Karlis Freimanis, Janis Riekstiņš and Janis Seskis – are discussed. The article covers the activities of the Latvian consulate in Klaipėda in 1920–1940; it analyses the changes in the ranks of the Latvian consulate, its personnel and the cultural activities of consuls.